No turning back: The history of feminism and the future of women - Freedman, Estelle B. (Ballantine Books, 2002)
Repeatedly declared dead by the media, the women’s movement has never been as vibrant as it is today. Indeed as Stanford professor and award-winning author Estelle B. Freedman argues in her compelling book, feminism has reached a critical momentum from which there is no turning back. Freedman examines the historical forces that have fueled the feminist movement over the past two hundred years–and explores how women today are looking to feminism for new approaches to issues of work, family, sexuality, and creativity. Drawing examples from a variety of countries and cultures, from the past and the present, this inspiring narrative will be required reading for anyone who wishes to understand the role women play in the world. Searching in its analysis and global in its perspective, No Turning Back will stand as a defining text in one of the most important social movements of all time.
Keywords: approches et analyses; discipline; fem1000; histoire; histoire des femmes*; histoire et politique; international; mouvements des femmes*; pratiques féministes; premier cycle; sciences humaines; sexisme; systèmes d'oppression; thématiques

Enjeux contemporains du féminisme indien - Haase-Dubosc, Danielle (Éditions de la Maison des sciences de l'homme, 2002)
Pour la première fois en français, un recueil d'essais témoigne des luttes et de la politique féministes en Inde, dans un contexte bien différent des problématiques occidentales. Inscrits dans la période contemporaine, de la turbulence des années 1960 et 1970 aux défis des années 1990, certains de ces textes ont été rédigés à chaud, d'autres sont plus rétrospectifs. Ils constituent un ensemble original à travers six grandes rubriques qui se complètent et se répondent l'une l'autre ... Tout en présentant les expériences historiques particulières qui ont nourri les théories et les pratiques du mouvement des femmes en Inde, cet ouvrage présente une approche vivante et engagée des questions actuellement en jeu pour les femmes indiennes.une vision plurielle du féminisme , dans une perspective transnationale respectueuse de l'altérité historique et culturelle
Keywords: 1900-1999; 1960-1969; 1970-1979; approches et analyses; asie; conflit; droits des femmes*; fem1000; histoire des femmes*; histoire et politique; inde; inégalités; mouvements des femmes*; premier cycle; périodes historiques; régions géographiques; systèmes d'oppression; thématiques